Perbedaan Tingkat Kecemasan Antara Pria Yang Bekerja Shift dan Non shift Di PT Tyfountex Kartasura Sukoharjo - Reeza, Mohammad Idzham; Indro N, I. G. B; Sulaeman, Endang Sutisna (Nexus Kedokteran Komunitas, 2013)
Background: Industrialization nowadays is a major source of anxiety among shift workers men and non shift workers men. The aim of this research is to acknowledge the anxiety level differences between shift workers men and non shift workers men. Methods: This study is an observational analytic cross sectional approach. The research sample was 20 men who are working during shift hours and 20 men who are working during non shift hours. The research instrument was used for L-scale of the MMPI and TMAS. Data analyzed by t test. Results: The results showed an average score of TMAS in shift workers men: 28,5 while in non shift workers men: 28,7. This data is not significant with slightly differences: (t: 0,079, p: 0,937). Conclusions: Researchers conclude there are no differences in anxiety level among men who are working during shift hours and non shift hours. Keywords: Anxiety, Shift Workers Men, Non Shift Workers Men